Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Pemasaran Relasional Sebagai Variabel Intervening : Studi Kasus Pada Dealer X Motor Yamaha Area Bogor - Irene Rafinadora Kristina; Son Diamar; Choiril Maksum (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
The purpose of this research is to find the influence of service quality and product quality to effect on customer loyalty with relationship marketing as a variable intervening (case study at dealer X on Bogor area). The research data collection uses the questioner spread to respondents. The population of this research is all customers of Dealer X Bogor area. The sampling method collection used in this research is non-probability sampling, with the collection technique is purposive sampling. The total sample of this research is 240 respondence. Calibration instrument to verify validity and reliability of each item. For each statement calculated with coefficient product-moment, and reliability calculated with coefficient alpha Cronbach. The analysis used in this research is Structural Equation Modelling (SEM) analysis technique. The results of this research show that service quality has an impact on relationship marketing, and product quality have an impact on relationship marketing. The conclusion is product quality has a higher value impact on relationship marketing than service quality. Service quality has an impact on customer loyalty, and product quality has an impact on customer loyalty. The conclusion is customer value has a higher value impact on customer loyalty than service quality. Purchase decisions have an impact on customer loyalty. As a whole viewed, which has the most impact on customer loyalty is relationship marketing. Based on this result of research, to increase customer loyalty need good service quality and good product quality so that improve relationship marketing between Dealer X and customer, and increase customer loyalty.